Strategic Alliances between Sharia Microfinance Institutions and Financial Technology in Strengthening Small Micro Enterprises (MSEs) - Euis Amalia; Indra Rahmatullah (Ekonomi Syariah IAIN Kudus, 2020)
Sharia microfinance and financial technology have a very significant role as an effective solution for accessing finance for small and micro-enterprises (MSEs). The research aims to investigate the business model used, type of contracts employed, other legal aspects, and the risk mitigation dimension involved. By utilizing qualitative methods and critically analyzing a specific case study related a business model by the alliances between PT Ammana Fintech Sharia and a sharia microfinance institution, BMT Syahida Ikaluin. In generating the data, interviews with several experts and practitioners. The study found that the business model used was based on crowdfunding, compliant with sharia principles dan has a strong basis both in positive law and Islamic edict (fatwa). The research showed that the strategic alliance between a sharia microfinance institution and financial technology is capable of strengthening access to capital sources for small and micro-enterprises. It also improves community financial literacy and financial inclusion. This research could contribute to the creation of innovative products concerning sharia microfinance and sharia financial technology. Furthermore, it could also become a benchmark in formulating policies to strengthen these strategic institutional alliances.